Entrepreneurship:: Kirznerians and Rothbardians - Gulisano, Adriano Gianturco (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
Kirznerian authors consider the pure entrepreneur an actor on alert that does not have some capital and discovers objective profit opportunities; different from Rothbardians, who claims the capitalist-entrepreneur as one who has capital, is subject to risk and seeks subjective opportunities. This article focuses on the active aspect of research and discovery, where opportunities are defined as such only when specifically explored. Better than anyone, the Kirznerian entrepreneur shows the feature of “arbitrage”, a dynamic concept formed by several successive instants in time, that goes from the perception to the enjoyment of a particular opportunity.